Die Atheisierung der Kultur im kommunistischen Polen - Biel, Robert J. (European Journal of Mental Health, 2013)
The Atheisation of Culture in Communist Poland and Its Present-Day Repercussions: The Age of Enlightenment marked the beginning of modern religious criticism in Europe. Several atheistic ideas born at that time have maintained their influence and affected the life and culture of many generations. This process, which clearly manifested itself in the People’s Republic of Poland as well, led to the atheisation of culture. The church in Poland has been acting as the patron of culture for centuries and this role was especially important at times of political dependence such as the division or the occupation of the country. Under the Communist rule, culture was given a subordinate status based on the structural and political principles of the Communist Party. Consequently, culture was primarily expected to serve communism. The intention of authorities to marginalise Christian culture and art resulted in its increasing ghettoisation. Following the declaration of a state of emergency (1981) the ghetto conditions created for Christian culture contributed to the so-called internal emigration of artists and the boycott of the Polish radio and television. This process generated an unofficial system of culture, which could cater to the needs of the majority of citizens. This unofficial system comprised actors and trustees of culture who were not subservient to state power or had more authority and freedom to represent different values, norms or forms of behaviour than those of the dominant cultural system. For example, churches or parish community rooms hosted theatre shows and other performances as well. The unofficial system of culture contributed to social integration in a significant way and helped to preserve national identity. The social status quo following the political turn compelled the Polish church to re-define its position on the free market of ethical, cultural and religious values and played a role in eliminating the gulf between the Christian message and modern society. Since church and culture have been deeply intertwined and Christians are conscious of their centuries-long spiritual and cultural heritage, they cannot and do not want to give up this unalterable element of national and religious identity. Christians have been forming the image of intangible culture for centuries and they will continue to strive for a position as equal and full partners in constructing the new European reality.